Facilitators and Barriers in Initiation of Breastfeeding within an Hour of Child Birth among Women at Selected Community (International Journal of Nursing Education, 2020)
Introduction: Most of the world’s new-born are left waiting too long to begin breastfeeding. In 2017, 78million new-borns were estimated to wait more than one hour to be put to the breast. This study aimed toassess the facilitators and barriers in initiation of breastfeeding within one hour of child birth.Methodology: A retrospective study was conducted at selected community in Chennai with a sample size of60 mothers through purposive sampling technique. Data was collected using demographic variable proforma,obstetrical variable proforma, checklist to assess the facilitators and barriers in initiation of breastfeedingwithin one hour of childbirth.Results: In initiation of breastfeeding Majority of the mothers felt antenatal preparation (100%) and supportfrom health professionals (54.4%) as Facilitators,96% of the mothers considered Pain during labour and newborns refused to feed as the barriers. There was significant association between initiation of breastfeedingwithin one hour of childbirth and selected Variables such as age of the mother (?2= 5.1428), knowledgeabout breastfeeding (?2=4.826) and source of information from health professionals (?2= 4.343, p>0.50).Conclusion: This study helps in understanding the facilitators and barriers in initiation of breastfeeding.By analysing these factors, Nurses and nursing students can step up to empower mothers to promote earlybreastfeeding.